On the Nature of the Mother-Infant Tie and Its Interaction With Freudian Drives - Kirsch, Michael; Buchholz, Michael B. (Frontiers in Psychology, 2020)
The affective bond between an infant and its caregiver, the so-called mother-infant tie, was analyzed by various reputable psychologists (e.g. Ainsworth, Clark, Erikson, Anna Freud, Harlow, Klein, Spitz, and Winnicott) but both the basic tenets of the bond and the importance of the trauma of maternal deprivation for personality disorders in adults were introduced by Bowlby. Although Bowlby was a trained psychoanalyst, he rejected central cornerstones of Freudian theory (esp. drive theory) and used concepts promulgated by renowned ethologists (Tinbergen and Lorenz) to establish his framework of “instinctive behavior” that has been developed further into the concept of “attachment theory” under the influence of Mary Ainsworth. However, since any precise experimental facts were lacking when Bowlby formulated his ideas on the concept of instinctive behavior, the whole framework is a descriptive, category-driven approach (like the ones of Freudian drives). In order to connect the mother-infant tie – as propounded by Bowlby – with experimental data, this manuscript undertakes a biochemical analysis of it because this strategy proved somewhat successful in relation to Freudian drives. The analysis unfolded that the neurochemical oxytocin, released by the action of sensory nerves, is of utmost importance for the operation of the mother-infant tie. Furthermore, multiple evidences have been presented to the fact that there is strong interaction between unconsciously operating Freudian drives and the consciously acting mother-infant tie (that is now classified as a drive). The outlined interaction in conjunction with the classification of attachment urges as drives gave a very detailed insight into how a SEEKING-derived reward can be evoked during operation of the mother-infant tie. In summary, there is no need to marginalize either the mother-infant tie or Freudian drives but rather there is need to respect both (principally different) impulses in moving towards a more extensive description.